Building a millionaire mindset : how to use the pillars of entrepreneurship to gain, maintain, and sustain long-lasting wealth - Wimbrey, Johnny (McGraw Hill, 2020)
"Become a first-generation millionaire using the groundbreaking mindset of entrepreneurial phenom Johnny Wimbrey From teenage felon to multi-millionaire in a just few short years after implementing his millionaire mindset principles . . The meteoric rise of Johnny Wimbrey is one of the great rags-to-riches / tragedy to triumph tales of our time. By seizing control of his life and developing a brand-new mindset, Wimbrey gave up the hard-core streets and a world of drugs, created a business that's now worth over nine-figures, and is presently living the life of a multi-millionaire with his family. Now, in Building a Millionaire Mindset, he provides the knowledge, tools, and insights you need to achieve your dreams-life-changing advice you can take to the bank, including: Participating in Your Own Rescue Being Busy versus Being Productive Realizing Someone Else's Mentality isn't Your Reality Becoming a Friend to Your Future Self Controlling Your Emotion Execute Versus Excuse Banishing Your Inner Try-baby Getting Off Your "But" Building a Millionaire Mindset avoids the overwhelmingly complex or pie-in-the sky approach of other books by providing a "building block" approach to entrepreneurial success: Each chapter provides a task you must complete before moving on. Entrepreneurs like you have opportunities and access to the technology and information past generations never imagined. And now you have access to the secrets of one of today's top entrepreneurs. Building a Millionaire Mindset delivers the mindset you need to launch your business to the million-dollar mark in no time flat"--